Preliminary study on properties of small diameter wild Acacia mangium species as potential biomass energy sources - Mohd Sukhairi Mat Rasat; Muhammad Iqbal Ahmad; Mohd Hazim Mohamad Amini; Razak Wahab; Puad Elham; Mohd Hafiz Jamaludin; Mohamad Faiz Mohd Amin; Nor Hakimin Abdullah (Universiti Malaysia Kelantan, 2016)
Currently, the primary energy supply in Malaysia is dominant by non-renewable energy sources such oil, natural gas and coal which contributed to the scarcity of these sources and occurrence of global warming. This phenomenon raises the public concerns to diversify the energy sources to sustain energy availability. To address these predicaments, biomass sources is among the prominent alternative energy sources since it is renewable and possesses minimal harms to the environment. Thus, the woody plant with high growth rate and high energy content that can be used to serve as potential biomass energy sources. In this study, small diameter (5-8cm) of wild Acacia mangium species have been determined and compared accordingly three (3) different portions (bottom, middle and top) and two (2) different particle sizes (0.5 and 1.5mm). The analysis conducted to determine the properties of raw material of Acacia mangium as biomass energy sources were proximate, physical and energy content properties. The result obtained for the energy content analysis of small diameter wild Acacia mangium has a mean calorific value range from 16.35 to 18.35MJ/kg between portions and particle sizes. In order to determine the effect of portions and particle sizes on each of the proximate, physical and energy content properties, two-way ANOVA was performed. It shows that both the portions and particle sizes have significant effect on calorific value (energy content) of small diameter wild Acacia mangium at 99% of confidence level. In a nutshell, the biomass energy properties of small diameter wild Acacia mangium with different portions and particle sizes were being determined.